ACTIVITY DISEQUILIBRIUM OF 230TH, 234238U IN OLD STILBITE: EFFECTS OF YOUNG U MOBILITY AND ?-RECOIL - Romer R.L.; Rocholl A. (My University, 2004)
Stilbite from Malmberget and Svappavara is part of hydrothermal mineral assemblages occupying regionally occurring open Palaeoproterozoic fractures in northern Sweden. At these locations, stilbite is characterized by Pbrad excess relative to U and by activity ratios of [234U]/[238U] > 1 and [230Th]/[238U] > 1. The activity disequilibrium requires a disturbance of the U-Th systematics within the last one million years. Leaching and infiltration experiments on Malmberget stilbite demonstrate: (i) preferential leaching in the order Pb >U >Th and uptake in the order Pb > U, and (ii) isotopic fractionation of U by preferential mobilization of 238U and 235U relative to 234U. Stepwise-leaching further indicates that the bulk of U is hosted in the channel sites of stilbite. The Th-U disequilibrium systematics observed in untreated Malmberget and Svappavara stilbite can be explained by: (1) addition of U with [234U]/[238U] > 1 from a fluid, or alternatively (2) loss of U from a two-component system, consisting of a component that is “open” or accessible and a component that is “closed” or inaccessible to mobilization. U addition requires a multistage history involving multiple gain or loss of U and/or Pb. In contrast, U loss does not necessarily require multistage processes but can also be explained by preferential removal of 238U (and 235U) relative to recoiled daughter isotopes such as 234U, 230Th, and 206Pb (and 207Pb) during a single event. Such a behavior could be obtained if the recoiled daughter isotopes of channel-sited uranium are implanted into the crystal lattice and, in such a way, become less mobile than their parent isotopes. This case implies an open-system behavior for ions in the channel sites and a closed-system behavior for ions in the silicate framework of stilbite. Each α-recoil directly or indirectly, i.e., through its recoil cascade, damages the silicate framework. Subsequent (continuous) low-temperature annealing of the damaged stilbite lattice could trap the recoiled daughter isotopes in the repaired crystal lattice or sealed-off channels. Such immobile recoiled material can, in part, represent the “closed” component of the system. This model can account for all observations regarding the Th-U-Pb systematics, including the Th-U disequilibrium systematics, the similarity in Th/U as deduced from Th-U disequilibrium and Pb isotope data, and the excess of radiogenic Pb (208Pb-parents also had been multiply recoiled). These two contrasting explanations involve either multistage or multicomponent systems. They do not permit the derivation of an accurate age.